PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJATERHADAP KEPUASAN KERJA KARYAWAN - Syarifatul Fajriyah (Universitas Mercu Buana, 2015)
Job satisfaction is important and need to be attention every organization, because human resource is the factor and the first cast in work process. Working without a satisfaction will make an employee be easy to complain, no spirit to work and difficult to get a reward. The object of this study is employee of PT. Bank Central Asia, Tbk. Cikarang Branch, Jawa Barat. This study was conducted on 60 respondents using qualitative descriptive approach. Therefore, the analysis of the data used is the statistical analysis in the form of multiple linear regression tests. The results of this study showed that partially and simultaneously, the variable of leadership style and work environment have effect on job satisfaction the employee of PT. Bank Central Asia, Tbk. Cikarang Branch, Jawa Barat. This is evidenced from the results of simultaneous test (F test) and partial test results (t-test) of both variant the variables of leadership style and work environment and showed significant value and support the hypothesis. Keywords: leadership style, job environment, job satisfaction